Linnaeus, Zoomusicology, Ecomusicology, and the Quest for Meaningful Categories - Marcello Sorce Keller (Muzikološki Zbornik, 2016)
“Music” is not a scientific term. In the course of time, it has become like a big container, where sonic objects and practices that have nothing in common are put together. It carries so many historical and cultural connotations as to make it unfit for scholarly discourse about the social use of sound.